2007
DOI: 10.1074/jbc.m704716200
|View full text |Cite
|
Sign up to set email alerts
|

Topology Inversion of SecG Is Essential for Cytosolic SecA-dependent Stimulation of Protein Translocation

Abstract: SecG, a subunit of the protein translocon, undergoes a cycle of topology inversion. To further examine the role of this topology inversion, we analyzed the activity of membrane vesicles carrying a SecG-PhoA fusion protein (SecG-PhoA inverted membrane vesicles (IMVs)). In the absence of externally added SecA, SecG-PhoA IMVs were as active in protein translocation as SecG ؉ IMVs per SecA. Consistent with this observation, insertion of membrane-bound SecA into SecG-PhoA IMVs was normally observed. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…We studied the significance of SecG inversion by means of IMV and mutant cells in which SecYEG in either the WT or a mutant form had been expressed at the WT level (9,(17)(18)(19)(20). Under the conditions used, MPIase could sufficiently interact with SecYEG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We studied the significance of SecG inversion by means of IMV and mutant cells in which SecYEG in either the WT or a mutant form had been expressed at the WT level (9,(17)(18)(19)(20). Under the conditions used, MPIase could sufficiently interact with SecYEG.…”
Section: Discussionmentioning
confidence: 99%
“…The major difference between this report and our study is that inverted membrane vesicles (IMV) either with an overproduced amount (23) or the WT level (our study) of SecYEG were used. Later, we found that SecG inversion cannot be reproduced under SecYEG overproduction conditions (18,23). Therefore, it is suggested that a factor or factors other than known Sec factors is required to invert SecG, as the factor should be limiting on SecYEG overproduction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, when each SecYEG with a Cys residue was reconstituted together with MPIase, the SecG dimer but not the SecE dimer was efficiently formed, indicating that MPIase transformed the back-to-back dimer into a side-by-side dimer ( Figure 5) (46). It has been reported that the SecG subunit of SecYEG, which significantly stimulates preprotein translocation (51-53), undergoes a topology inversion cycle coupled with preprotein translocation (54)(55)(56)(57). It has also been demonstrated that this remarkable structure change of SecG is essential for the SecG function (54,56).…”
Section: Mechanism Of the Sec-dependent Reactionmentioning
confidence: 99%